Orientational bistability and first order phase transitions in liquid crystalline nanosuspensions - Zakhlevnykh, A.N.; Petrov, D.A. (Perm Federal Research Centre Journal, 2017)
In the framework of continuum theory threshold transitions induced by a magnetic field in compensated and usual (magnetized) ferronematics, i.e., suspensions of monodomain magnetic particles in nematic liquid crystals are studied. Analytical expressions for the threshold fields of orientational transitions between coexisting phases are obtained. It is shown that the transitions between non-uniform and uniform states can be the first or second order phase transitions in the dependence on the intensity of segregation effects.